THE EFFECT OF PRECIPITATION ON MICROSTRUCTURE AND CORROSION BEHAVIOUR OF ZK60 SUBJECTED TO SEVERE PLASTIC DEFORMATION AS BIODEGRADABLE MATERIAL - Muhammad Rifai (Metalurgi, 2021)
Microstructure and corrosion behaviour of ZK60 subjected to severe plastic deformation (SPD) as biodegradable material has been investigated in terms of grain refinement process and precipitation formation. Equal channel angular pressing (ECAP) was one of the well-known SPD techniques due to their advantages to promote dislocation and grain fragmentation. ZK60 billet was cut to a 10 mm diameter cylindrical shape for biodegradable material application. ECAP process was carried out up to two passes by Route Bc at 423 K temperature process. Microhardness test was performed at ECAP processed sample, and the structure observation was carried by optical microscope and transmission electron microscope. The corrosion behaviour of the material was investigated by an anodic polarization curve. The ECAP process promotes dislocation accumulation efficiently and ultrafine-grained structure formation. It may improve the formability characteristic of ZK60. The hardness also showed significant increment during the ECAP process due to the high level of deformation. Corrosion behaviours and microstructure observation during the ECAP process showed a correlation that concluded that grain refinement and precipitation formation influenced the electrochemical properties. The alloying element such as Zn and Zr promoted the protective film for corrosion due to their ability for pitting protection. ECAP improved the precipitation formation for corrosion resistance, microstructure uniformity and material formability.